2018
DOI: 10.3390/fermentation4020028
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Flocculation—Sedimentation and Flotation

Abstract: Unlike most fermentation alcohol beverage production processes, brewers recycle their yeast. This is achieved by employing a yeast culture's: flocculation, adhesion, sedimentation, flotation, and cropping characteristics. As a consequence of yeast recycling, the quality of the cropped yeast culture's characteristics is critical. However, the other major function of brewer's yeast is to metabolise wort into ethanol, carbon dioxide, glycerol, and other fermentation products, many of which contribute to beer's ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 115 publications
1
24
0
1
Order By: Relevance
“…The WT, ydr131cΔ, atg1Δ and ydr131cΔatg1Δ cells grown in YPD medium overnight and observed for floc formation visually and using microscope. The dependence of the floc formation on EDTA was tested by adding the 30mM of EDTA (chelating agent) to growth medium (S tewart 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The WT, ydr131cΔ, atg1Δ and ydr131cΔatg1Δ cells grown in YPD medium overnight and observed for floc formation visually and using microscope. The dependence of the floc formation on EDTA was tested by adding the 30mM of EDTA (chelating agent) to growth medium (S tewart 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effect in oil recovery observed by the addition of CaCl 2 in centrifugation and not in GEOR can be explained by the fact that the calcium ions not only shield electrostatic repulsions but can also create links between the proteins surrounding the oil droplets. The creation of flocs of biomass when using CaCl 2 during fermentation broth has been demonstrated for Saccharomyces cerevisae (Nayyar et al, 2017;Stewart, 2018), however, no literature was found regarding E. coli fermentations with CaCl 2 flocculant. This seems to be confirmed by the microscopic pictures shown in Fig.…”
Section: Comparison Of Three Enhancement Oil Recovery Methods When Using Flocculants During Fermentation At Lab Scalementioning
confidence: 99%
“…involved in aging, oxidative stress response, and regulation of mitochondrial biogenesis [9] anchored to the cell by disulphide bridge [9] involved in remodeling of cell wall during culture development and stress/degradation responses [9] Sim1 cell wall remodeling during culture development [10,11] hpf1p haze protective mannoprotein [12] ecm33 required for cell wall integrity and assembly of the mannoprotein outer layer of the cell wall [6] cwp1 linked to β-1,3 and β-1,6-glucan through a phosphodiester bond [5] Does not require gPi anchor [5] cis3 component of outer cell wall layer for cell wall stability and optimal growth [10] Flocculation proteins flo1 flocculation inhibited by mannose residues [13] flo5 loss of gene flo5, requires propagation culture to be replaced [13] flo9…”
Section: Cell Wall Mannoproteins Uth1mentioning
confidence: 99%
“…Small flocculation protein [13] flo11 involved in filamentous, chain formation growth and flor forming then flocculation [13] Table 4. lc-Qtof-mS instrument parameters.…”
Section: Cell Wall Mannoproteins Uth1mentioning
confidence: 99%